Modeling of Static Characteristics of Switched Reluctance Motor - Ali Asghar Memon; Imtiaz Hussain; Jawaid Daudpoto (Mehran University Research Journal of Engineering and Technology, 2013)
To investigate the running characteristics of a switched reluctance motor, the static characteristics and related input data tables are required. The static characteristics comprise of flux linkage, co-energy and static torque characteristics. The co-energy and static torque are calculated once data of magnetization characteristics is available. The data of co-energy is required for the calculation of static torque characteristics. The simulation model includes the data of static characteristics for prediction of the instantaneous and steady state performance of the motor. In this research a computer based procedure of experiments is carried out for measurement of the magnetization characteristics. For every set of measurements, the removal of eddy current is carefully addressed. The experiments are carried out on an existing 8/6 pole rotary switched reluctance motor. Additionally, the instantaneous phase current, instantaneous torque and flux waveforms are produced by using linear, which is by default and spline data interpolation separately. The information obtained from theses simulation results will help in an improved simulation model for predicting the performance of the machine.